2019
DOI: 10.3390/sym11030353
|View full text |Cite
|
Sign up to set email alerts
|

A New Hybrid MCDM Model: Sustainable Supplier Selection in a Construction Company

Abstract: Sustainable development is one of the most important preconditions for preserving resources and balanced functioning of a complete supply chain in different areas. Taking into account the complexity of sustainable development and a supply chain, different decisions have to be made day-to-day, requiring the consideration of different parameters. One of the most important decisions in a sustainable supply chain is the selection of a sustainable supplier and, often the applied methodology is multi-criteria decisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(67 citation statements)
references
References 59 publications
0
64
0
3
Order By: Relevance
“…Considering the overall correlation coefficient of 0.945, it can be concluded that the rankings of the alternatives are in very high correlation since all values above 0.80 can be characterized as such [27]. As already noted, MARCOS, SAW, and ARAS are consistent and are in complete correlation SCC = 1.000, i.e., no alternative changes rank.…”
Section: Sensitivity Analysis and Discussionmentioning
confidence: 66%
“…Considering the overall correlation coefficient of 0.945, it can be concluded that the rankings of the alternatives are in very high correlation since all values above 0.80 can be characterized as such [27]. As already noted, MARCOS, SAW, and ARAS are consistent and are in complete correlation SCC = 1.000, i.e., no alternative changes rank.…”
Section: Sensitivity Analysis and Discussionmentioning
confidence: 66%
“…Due to strict government requests and the huge stress from the public, the consideration of supply chain sustainability was increased [36]. Sustainable development is one of the most significant conditions of saving resources and keeping the supply chain phases operating efficiently [57]. This explains why SSCM became one of the most important competitive strategies in organizations [58].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the methodological procedure of FUCOM eliminates the problem of redundancy of pairwise comparisons of criteria, which exists in some subjective models for determining the weights of criteria. FUCOM has been used in many applications such as forklift selection (Fazlollahtabar et al, 2019), ranking the airlines (Badi and Abdulshahed, 2019), service quality measurments (Prentkovskis et al, 2018), occupational safety and health climate (Stefanović et al, 2019), service quality of rail transprort (Đorđević et al, 2019), and supplier selection (Durmić, 2019); (Matić et al, 2019). Assume that there are n evaluation criteria in a multi-criteria model that are designated as wj, j = 1,2, ..., n, and that their weight coefficients need to be determined.…”
Section: Methodsmentioning
confidence: 99%